Adenoid Cystic Carcinoma of the Nasopharynx with Skull Base Involvement: Retrospective National Cohort Analysis of Treatment Paradigms, Outcomes, and Provider Density - Gadkaree, Shekhar K.; Parikh, Anuraag S.; Barbarite, Eric; Feng, Allen L.; McCarty, Justin; Gray, Stacey T.; Lin, Derrick T. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives This article examines a national cohort of patients with nasopharyngeal adenoid cystic carcinoma (ACC) for incidence, skull base invasion, overall survival, and treatment paradigms.Design, Setting, and Participants Retrospective national population-based study using Surveillance, Epidemiology, and End Results program data of patients with ACC of the nasopharynx (NACC) and skull base between 2004 and 2016.Main Outcomes and Measures Primary outcomes included 5-year overall survival and odds of radiation treatment. Statistical analysis was performed using STATA 15.0 (STATACorp). p-Values < 0.05 were considered statistically significant.Results Of the 2,385 cases of ACC, 70 cases were classified as NACC. Twenty-one percent (15) involved invasion of the skull base or posterior pharyngeal wall, and 42% (30) were either stage 3 or stage 4. The 5-year overall survival for patients with NACC without skull base invasion was 67% which dropped to 40% with invasion into the skull base. Radiation was used as the primary form of therapy for 62% of NACC and 73% of NACC invading into skull base. Odds of receiving radiation therapy and 5-year survival were not affected by socioeconomic status or density of providers.Conclusion NACC is rare in incidence and was most commonly treated with radiation therapy when advanced in stage. Prognosis was dependent on invasion through posterior pharyngeal wall and skull base. Provider density and socioeconomic status did not affect odds of radiation or overall survival for NACC.
Keywords: nasopharyngeal malignancy; adenoid cystic carcinoma; skull base; radiation therapy; outcomes